Western view of San Jose from the Medico-Dental Building - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of the City of San Jose, taken from the Medico-Dental Building, looking west down Santa Clara street. Buildings depicted in the image include the Bank of America, in the far center of the image.